2020
DOI: 10.2166/nh.2020.100
|View full text |Cite
|
Sign up to set email alerts
|

The exploration of a Temporal Convolutional Network combined with Encoder-Decoder framework for runoff forecasting

Abstract: The Temporal Convolutional Network (TCN) and TCN combined with the Encoder-Decoder architecture (TCN-ED) are proposed to forecast runoff in this study. Both models are trained and tested using the hourly data in the Jianxi basin, China. The results indicate that the forecast horizon has a great impact on the forecast ability, and the concentration time of the basin is a critical threshold to the effective forecast horizon for both models. Both models perform poorly in the low flow, and goodwell in the medium a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Similarly, LightGBM has performed well in financial forecasting and cancer patient classification [36] [37]. Although TCN is a recently proposed model, it is also widely used in the fields of the weather forecasting [38], runoff forecasting [39], etc.…”
Section: ) Methods For Comparisonmentioning
confidence: 99%
“…Similarly, LightGBM has performed well in financial forecasting and cancer patient classification [36] [37]. Although TCN is a recently proposed model, it is also widely used in the fields of the weather forecasting [38], runoff forecasting [39], etc.…”
Section: ) Methods For Comparisonmentioning
confidence: 99%
“…In this study, the VIC model was verified through a comparison between the simulated stream flows and the observations. The Nash-Sutcliffe efficiency (NSE), relative error (Bias), and determination coefficient (R 2 ) were used for the evaluation of model accuracy (Zhou et al 2019(Zhou et al , 2020Kao et al 2020;Lin et al 2020). A significant coincidence rate with P , 0.05 was detected in both the calibration and validation (Figure 2), demonstrating that the VIC-based ETa is adaptable and rational for the subsequent drought analysis.…”
Section: Vic Modelmentioning
confidence: 98%
“…With gated TCN layers, Deep Mind researchers developed a model named WaveNet for the speech recognition of the voice wave. And recent studies have shown that TCN models work well on rainfall-runoff modeling as well (Lin et al, 2020; Van et al, 2020;Xu et al, 2021). However, these studies developed lumped models by considering each watershed as a unit, and all available geospatial information is not used.…”
Section: Introductionmentioning
confidence: 96%